2014
DOI: 10.18632/oncotarget.2871
|View full text |Cite
|
Sign up to set email alerts
|

Mislocalization of p27 to the cytoplasm of breast cancer cells confers resistance to anti-HER2 targeted therapy

Abstract: As a cell cycle inhibitor and tumor suppressor, p27 is frequently misregulated in human cancers. Increased degradation is the most common mechanism of misregulation, however in some cancers, p27 is mislocalized from its cell cycle inhibitory location in the nucleus, to the cytoplasm. In normal cells cytoplasmic p27 has functions that are distinct from its cell cycle-regulatory nuclear functions. Therefore, an important question is whether localization of p27 to the cytoplasm in tumor cells is primarily a mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…p27 is a nuclear protein with a tumor suppressive role, but oncogenic signal-mediated cytoplasmic retention and nuclear export of p27 results in enhanced oncogenic activity 28,38 or drug resistance. 26 Once translocated to the cytoplasm, p27 will gain the function of promoting cancer cell migration and invasiveness. 38 Thus, cytosolic p27 has a metastasis promoting function opposite to the tumor suppressor role of nuclear p27.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p27 is a nuclear protein with a tumor suppressive role, but oncogenic signal-mediated cytoplasmic retention and nuclear export of p27 results in enhanced oncogenic activity 28,38 or drug resistance. 26 Once translocated to the cytoplasm, p27 will gain the function of promoting cancer cell migration and invasiveness. 38 Thus, cytosolic p27 has a metastasis promoting function opposite to the tumor suppressor role of nuclear p27.…”
Section: Discussionmentioning
confidence: 99%
“…17 p27 is regulated by many oncogenic signals for facilitating cell cycle progression. [18][19][20][21][22][23][24][25][26] Protein levels of p27 are tightly controlled for cell cycle progression, 16,17,27 and p27 levels are positively regulated by the activity of many tumor suppressors. 22,28 As a negative regulator of the cell cycle, p27 is also functioning like a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…This regulation is incorrectly activated in chronic myelogenous leukemia and breast cancer [50,51]. In addition, phosphorylation of this domain at a threonine is related to increased metastatic processes and cell migration [52,53]. The p27-KID is an IDP [54,55].…”
Section: The Af4-af9 Protein System: Another Complex Formed In Fusionmentioning
confidence: 99%
“…Additionally, a recent study has shown that cytoplasmic mislocalization of p27 in HER2-positive breast cancer cells causes resistance to lapatinib, a dual EGFR-HER2 inhibitor. 47 Therefore, it will be also interesting to determine in the future whether Pfn1 expression has any effect on p27 localization and therapeutic resistance in HER2-positive breast cancer cells. Finally, our finding that Pfn1 overexpression stimulates AMPK activation has much broader implications in the context of cancer beyond and above p27 regulation.…”
Section: Cells 11 R-cadherin Expression Is Often Associated With Indmentioning
confidence: 99%